Modified activated carbon, silicon-carbon composite material, preparation method of silicon-carbon composite material, pole piece, application and electrochemical device
The silicon-carbon composite material was prepared by microwave reaction modified activated carbon and combined with vapor deposition method, which solved the problem of poor battery capacity performance caused by insufficient micropore ratio of activated carbon, and achieved high capacity performance and small expansion effects.
Patent Information
- Application Number
- CN202411766873.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-12-03
AI Technical Summary
In the prior art, the small proportion of activated carbon micropores leads to poor battery capacity performance of silicon-based composite materials, and the preparation method is complicated, which is not conducive to industrial production.
By microwave reaction of activated carbon with solvent, modified activated carbon with large micropore volume and micropore proportion was prepared. Silane was deposited into the modified activated carbon in combination with vapor deposition method to prepare silicon-carbon composite material.
It is achieved to improve the capacity performance of the battery while maintaining better first-time Coulomb efficiency and small expansion, and meet the commercial application level.
Smart Images

Figure CN119503795A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a modified activated carbon, a silicon-carbon composite material, a preparation method thereof, a pole piece, an application and an electrochemical device. Background Art
[0002] Silicon-based anode materials have become one of the most promising anode materials for lithium-ion batteries due to their theoretical specific capacity that is about 10 times higher than that of graphite, low lithium insertion potential, abundant natural resources and environmental friendliness. However, the volume expansion and contraction of silicon-based anode materials during lithium-ion charging and discharging may lead to the destruction of the electrode structure, and the low intrinsic conductivity has hindered their practical application to a certain extent. The volume expansion of silicon-based anode materials exceeds 300% when fully lithiated during the silicon-lithium alloying process, which may cause problems such as degranulation and cracking between electrode particles in silicon-based materials during the cycle, reducing the cycle stability and service life of the battery, and even causing battery failure. In response to the above problems, many methods have been designed to improve their large expansion. For example, reducing the size of silicon particles to the nanometer level, preparing silicon-based anode materials with porous structures, surface modifying silicon particles, encapsulating them in materials with high elasticity and stability, and compounding silicon with other materials can all reduce the volume expansion effect of silicon-based anode materials. Non-metals, metals and their oxides, silicon oxides, organic polymers and various carbon materials have been tried to be compounded with silicon. Among them, the composite of carbon materials and silicon is the most commonly used and effective method. The mechanical and electrical properties of carbon materials can make up for the defects of silicon. The carbon matrix in the silicon / carbon composite material has good electrical conductivity, which can effectively promote electron transfer and diffusion of lithium ions, and improve the cycle stability during charging and discharging. The addition of carbon materials promotes the dispersion of Si particles, and good elasticity and flexibility can adapt to volume changes and effectively buffer the volume expansion effect of silicon particles. Nevertheless, with the rapid development of electric vehicles and portable electronic devices, their conductivity and cycle stability still need to be improved, and the electrochemical performance still needs to be further optimized. Therefore, the development of a low-expansion, high-conductivity silicon-carbon negative electrode material has very important practical applications and research value.
[0003] The patent with publication number CN117317188A discloses a method for preparing an activated carbon composite negative electrode material coated with nano-silicon dioxide, which uses sodium hydride as a catalyst, and replaces octachloromethyl cage silsesquioxane and 2-(2-naphthyl)-1H-benzimidazole to obtain naphthylbenzimidazole cage silsesquioxane, and then contains benzene rings and naphthalene ring structures, which are cross-linked and polymerized with dimethoxymethane under the catalysis of ferric chloride, and then calcined in a high-temperature tubular furnace to obtain an activated carbon negative electrode material coated with nano-silicon dioxide. Among them, nano-silicon dioxide is coated with porous carbon, which alleviates the volume expansion phenomenon of nano-silicon dioxide during charge and discharge, and improves the structural stability of the negative electrode. However, its preparation method is complicated, which is not conducive to industrial production, and the specific capacity and cycle performance of the composite material are particularly limited, and the capacity and conductivity of silicon dioxide are low, which limits its better application in the electronic market.
[0004] The patent with publication number CN107910540A discloses a method for preparing a silicon-carbon negative electrode material in which silicon material is embedded in the gaps of activated carbon. The method comprises adding activated carbon and silicate into water, stirring evenly, wherein the particle size of the activated carbon is 0.1-30 μm; adding an acid solution, stirring, washing, and drying; introducing hydrogen, and cooling after the reaction is complete to obtain a carbon-silicon negative electrode material. Among them, the silicon material is embedded in the gaps of the activated carbon by precipitation, reduction, and the like, and the obtained carbon-silicon negative electrode material has a stable structure and can be used to prepare lithium-ion batteries with good conductivity, high specific capacity, and long cycle life. However, the prepared silicon-carbon composite material has large differences in shape and size, which may cause differences in the electron transmission and ion diffusion rates of different parts, and may experience different degrees of volume changes and stress effects, which in turn have a significant impact on its electrochemical performance and cycle stability.
[0005] Therefore, how to provide a new modified activated carbon / silicon composite material to improve the conductivity of the electrode material, and to compound a conductive, hard and tough coating layer, and finally prepare a silicon-carbon negative electrode material that can effectively buffer volume expansion, is a key challenge faced by the current work. Summary of the invention
[0006] The technical problem to be solved by the present invention is to overcome the defect in the prior art that the small proportion of micropores of activated carbon leads to a small amount of silane adsorption, resulting in poor capacity performance of batteries assembled from the obtained silicon-based composite materials, and provide a modified activated carbon, silicon-carbon composite material and its preparation method, pole piece, application and electrochemical device. The modified activated carbon of the present invention has a large micropore volume and micropore ratio. The battery assembled from the silicon-carbon composite material prepared from the modified activated carbon can achieve better capacity performance while maintaining better first coulomb efficiency and less expansion, which can greatly meet the level of commercial application.
[0007] The present invention solves the above technical problems through the following technical solutions.
[0008] The present invention provides a method for preparing modified activated carbon, which comprises the following steps:
[0009] The activated carbon and the solvent are subjected to microwave reaction to obtain modified activated carbon; the microwave power during the microwave reaction is 600-800W; and the microwave reaction time is 10-40min.
[0010] In the present invention, the specific surface area of the activated carbon can be 1100-1150m 2 / g. The micropore volume of the activated carbon may be 300-360mm 3 / g. Micropore volume is the volume of micropores (pores with a pore size less than 2nm) in unit mass of activated carbon.
[0011] In the present invention, the activated carbon can be obtained by conventional preparation methods in the art, preferably by the following method: pre-oxidizing, carbonizing and activating the phenolic resin, wherein the temperatures of the pre-oxidation, carbonization and activation are increased sequentially.
[0012] The phenolic resin may be conventional in the art, for example, phenolic resin model 2123 purchased from Shandong Jiaqi Chemical Co., Ltd.
[0013] The pre-oxidation temperature may be 120-140° C., such as 130° C. The pre-oxidation time may be 1-3 hours, such as 2 hours. The pre-oxidation is preferably carried out in air or oxygen atmosphere.
[0014] Wherein, the carbonization is preferably carried out under an inert atmosphere. The inert atmosphere is preferably nitrogen. The gas flow rate of the inert atmosphere may be 10-30 mL / min, for example 20 mL / min. The temperature of the carbonization may be 500-600°C, for example 550°C. The time of the carbonization may be 0.5-1.5 h, for example 1 h. The rate of heating from the pre-oxidation temperature to the carbonization temperature may be 3-5°C / min, for example 4°C / min.
[0015] Wherein, after the carbonization and before the activation, it is preferred to further include the steps of cooling and grinding. The end point of the cooling can be room temperature, generally 20-30° C. The particle size of the material after the grinding is 60 mesh to 80 mesh.
[0016] Wherein, the activation is preferably carried out under an inert atmosphere. The inert atmosphere is preferably nitrogen. The gas flow rate of the inert atmosphere may be 10-30 mL / min, for example 20 mL / min. The activation temperature may be 600-700°C, for example 650°C. The activation time may be 0.5-1.5 h, for example 1 h. The activation atmosphere is preferably water vapor. The rate of heating from room temperature to the activation temperature may be 2-4°C / min, for example 3°C / min.
[0017] In the present invention, before subjecting the activated carbon to microwave reaction, it is preferred to further perform washing and drying steps.
[0018] Wherein, the washing operation can be conventional in the art, for example, washing with distilled water, inorganic acid and distilled water in sequence. The type of the inorganic acid can be conventional in the art, such as nitric acid. During the washing, an inorganic acid aqueous solution is generally used. The mass percentage of the inorganic acid in the inorganic acid aqueous solution can be 2%. The end point of the washing is preferably neutral, generally a pH of 7.0.
[0019] The drying operation may be conventional in the art, such as drying in an oven. The drying temperature may be 110-130°C, such as 120°C.
[0020] In the present invention, the type of the solvent can be conventional in the art, such as water or an alcohol solvent. The alcohol solvent is preferably one or more of isopropanol, ethylene glycol, propylene glycol and n-butanol, such as n-butanol.
[0021] In the present invention, the mass volume ratio of the activated carbon to the solvent may be 1 g: (1-5) mL, preferably 1 g: (2-4) mL, for example 1 g: 3 mL.
[0022] In the present invention, the microwave power during the microwave reaction is preferably 650-750W, such as 700W.
[0023] In the present invention, the temperature of the microwave reaction is preferably 60-90°C, such as 80°C.
[0024] In the present invention, the microwave reaction time is preferably 20-30 min, such as 25 min.
[0025] In the present invention, the microwave reaction preferably further includes cooling, washing and drying steps.
[0026] The cooling operation may be conventional in the art, such as natural cooling. The cooling end temperature may be room temperature, generally 20-30°C.
[0027] The washing operation may be conventional in the art, such as centrifugal washing with deionized water.
[0028] The drying operation may be conventional in the art, such as drying in a constant temperature drying oven. The drying temperature may be 50-70° C., such as 60° C. The drying time may be 20-30 h, such as 24 h.
[0029] In the present invention, guanidine salt is preferably added during the microwave reaction.
[0030] Wherein, the guanidine salt is a salt compound generated by the reaction of guanidine and acid, preferably guanidine hydrochloride, guanidine nitrate, guanidine sulfate or guanidine carbonate. The guanidine hydrochloride is preferably aminoguanidine hydrochloride, 1,3-diaminoguanidine hydrochloride or 1-methylguanidine hydrochloride. The guanidine sulfate is preferably 1,3-diphenylguanidine sulfate or 1-(4-aminobutyl)guanidine sulfate. The guanidine carbonate is preferably 4-chlorophenylguanidine carbonate or phenylguanidine carbonate.
[0031] The mass ratio of the activated carbon to the guanidine salt is preferably (3-22):1, more preferably (4-21):1, such as 10:1, 20:1, 6.67:1 or 5:1.
[0032] In the present invention, potassium carbonate is preferably added during the microwave reaction.
[0033] Wherein, the mass ratio of the activated carbon to the potassium carbonate is preferably (5-15):1, for example 10:1.
[0034] In the present invention, when guanidine salt and potassium carbonate are added during the microwave reaction, it is preferred to first mix and stir the guanidine salt, potassium carbonate and solvent, cool them down, and then add the activated carbon. The temperature of the mixing and stirring can be 50-70°C, for example, 60°C. The time of the mixing and stirring is 0.5-1.5h, for example, 1h. The end point of the cooling can be room temperature, generally 20-30°C.
[0035] The present invention also provides a modified activated carbon, which is prepared by the preparation method of the modified activated carbon as described above.
[0036] In the present invention, the specific surface area of the modified activated carbon can be 1750-2000m 2 / g, such as 1784.3, 1878.3, 1834.2, 1798.3, 1794.1, 1884.5, or 1939.4m 2 / g.
[0037] In the present invention, the micropore volume of the modified activated carbon can be 0.5-0.9 cm 3 / g, for example 0.579, 0.606, 0.583, 0.588, 0.563, 0.598 or 0.637 cm 3 / g. Micropore volume refers to the volume of pores with a pore size of less than 2nm per unit mass of modified activated carbon.
[0038] In the present invention, the micropore ratio of the modified activated carbon may be 78%-86%, such as 79.3%, 81.4%, 78.9%, 79.3%, 79.4%, 81.0% or 84.6%. The micropore ratio represents the percentage of the volume of pores with a pore diameter of less than 2 nm in a unit mass of the modified activated carbon to the total pore volume of the modified activated carbon.
[0039] In the present invention, the mesopore ratio of the modified activated carbon may be 10%-25%, for example, 20.38%, 20.25%, 17.25%, 19.10%, 19.38%, 18.5% or 14.9%. The mesopore ratio represents the percentage of the volume of pores with a pore size greater than 2.5 nm and less than 50 nm in the unit mass of the modified activated carbon to the volume of all pores of the modified activated carbon.
[0040] In the present invention, the macropore ratio of the modified activated carbon may be 0.2%-2.3%, such as 1.32%, 1.35%, 0.35%, 2.00% or 0.50%. The macropore ratio represents the percentage of the volume of pores with a pore diameter greater than 50 nm in the unit mass of the modified activated carbon to the volume of all pores of the modified activated carbon.
[0041] In the present invention, the guanidine content of the modified activated carbon may be 0-0.12, such as 0.04, 0.06, 0.09, 0.10, 0.07 or 0.08.
[0042] In the present invention, the amino content of the modified activated carbon may be 0-3.00, for example, 1.53, 1.75, 2.08, 2.46, 2.03 or 2.57.
[0043] In the present invention, the nitrogen content of the modified activated carbon may be 0.10%-7.00%, such as 0.36%, 4.35%, 5.14%, 5.84%, 6.63%, 4.84% or 5.52%. The nitrogen content represents the percentage of the mass of the nitrogen element to the mass of the modified activated carbon.
[0044] The present invention provides a method for preparing a silicon-carbon composite material, which comprises the following steps: vapor-depositing the modified activated carbon and silane as described above to obtain the silicon-carbon composite material.
[0045] In the present invention, the vapor deposition equipment may be conventional in the art, such as a fluidized bed.
[0046] In the present invention, the temperature of the vapor deposition may be 400-600°C, for example 500°C.
[0047] In the present invention, the vapor deposition time may be 300-400 min, for example 330 min.
[0048] In the present invention, the rate of heating from room temperature to the vapor deposition temperature may be 2-4° C. / min, for example, 3° C. / min.
[0049] In the present invention, the mass volume ratio of the modified activated carbon to the silane may be 1 kg: (3000-12000) L, for example, 1 kg: 6000 L or 1 kg: 6600 L.
[0050] In the present invention, after the modified activated carbon and silane as described above are subjected to vapor deposition to obtain the silane composite material A, a step of coating with MXene material or carbon is preferably further included.
[0051] Wherein, when MXene material is used for coating, the mass ratio of the silane composite material A to the MXene material may be 1:(0.2-0.8), for example, 1:0.4 or 1:0.6.
[0052] Wherein, the silane composite material A and the MXene material are preferably ball-milled before the MXene material is coated. During the ball milling, the rotation speed may be 500-700rpm, for example, 600rpm. The ball-to-material ratio may be (20-30):1, for example, 25:1. The ball milling time may be 40-56h, for example, 48h. The ball milling is preferably carried out in a ball milling jar. Balls are generally added to the ball milling. The material of the ball milling jar and the balls is preferably natural agate. The diameter of the balls may be 6-8nm.
[0053] The MXene material can be obtained from a commercial source or prepared by a conventional method in the art, preferably by the following method: Ti 3 AlC 2 The aluminum layer in the tube can be etched.
[0054] The Ti 3 AlC 2 The particle size may be 300-500 mesh, for example 400 mesh.
[0055] The etching solution is preferably an acid solution of sodium fluoride. The acid solution is preferably an aqueous solution of an inorganic acid, such as an aqueous solution of hydrochloric acid. The molar concentration of the acid solution may be 8-10 M, such as 9 M. In the acid solution of sodium fluoride, the ratio of sodium fluoride to acid may be 1 g: (0.2-0.25) mol, such as 1 g: 0.225 mol.
[0056] The Ti 3 AlC 2The mass ratio of the sodium fluoride to the sodium fluoride may be 1:(1-3), for example 1:2.
[0057] The etching is preferably performed in a water bath. The etching temperature may be 30-60° C., such as 40 or 60° C. The etching time may be 40-56 h, such as 48 h.
[0058] Preferably, a centrifugal step is further included after the etching. The centrifugal speed may be 3000-4000 rpm, for example 3500 rpm.
[0059] Wherein, when MXene material is used for coating, the coating method is preferably vapor deposition. The coating is preferably carried out under an inert atmosphere. The inert atmosphere is preferably nitrogen.
[0060] When MXene material is used for coating, the coating temperature may be 400-600° C., for example, 500° C. The rate of heating from room temperature to the coating temperature may be 4-6° C. / min, for example, 5° C. / min. The coating time may be 1-3 h, for example, 2 h.
[0061] Wherein, when carbon coating is adopted, the coating method is preferably gas phase coating. During the gas phase coating, the carbon source may be a conventional gas carbon source in the art, preferably acetylene. The gas carbon source is preferably also introduced with a carrier gas. The type of the carrier gas is preferably nitrogen. The volume ratio of the gas carbon source and the carrier gas may be (1-3):1, for example, 2:1. The mass volume ratio of the silicon-carbon composite material and the carbon source may be 1g:(1000-2000)L, for example, 1g:1440L. The temperature of the carbon coating may be 500-560°C, for example, 560°C. The time of the carbon coating may be 10-14h, for example, 12h. The rate of heating from room temperature to the temperature of the carbon coating may be 2-4°C / min, for example, 3°C / min.
[0062] The present invention provides a silicon-carbon composite material, which is prepared by the preparation method of the silicon-carbon composite material as described above.
[0063] In the present invention, the yield of the silane composite material may be 24%-32%, for example, 30%, 29%, 28%, 27% or 26%.
[0064] In the present invention, the specific surface area of the silane composite material can be 4.0-5.4m 2 / g, such as 4.1, 4.2, 4.6, 4.7, 4.8, 4.9, 5.0, 5.1 or 5.3m 2 / g.
[0065] In the present invention, the D50 of the silane composite material may be 7.5-8.7 μm, for example, 8.6, 8.5, 8.4, 8.3, 8.0, 7.9 or 7.8 μm.
[0066] In the present invention, the interlayer spacing of the silane composite material may be 0.2-0.4, for example, 0.301, 0.299, 0.298, 0.296, 0.293, 0.291, 0.287, 0.285, 0.283, 0.279, 0.269 or 0.267.
[0067] In the present invention, the micropore volume of the silane composite material can be 0.4-0.8cm 3 / g, for example, 0.749, 0.747, 0.746, 0.692, 0.672, 0.678, 0.648, 0.618, 0.616, 0.608, 0.593, 0.579, 0.511 or 0.496. The micropore volume refers to the volume of pores with a pore diameter less than 2 nm in a unit mass of the silane composite material.
[0068] The present invention also provides a pole piece, which comprises the silicon-carbon composite material as described above.
[0069] In the present invention, preferably, the electrode sheet is a negative electrode sheet.
[0070] The present invention also provides an application of the pole piece as described above in an electrochemical device.
[0071] The present invention also provides an electrochemical device, which comprises the pole piece as described above.
[0072] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.
[0073] The reagents and raw materials used in the present invention are commercially available.
[0074] The positive and progressive effects of the present invention are:
[0075] The modified porous activated carbon prepared by the present invention has a large micropore volume. The battery assembled with the silicon-carbon composite material prepared by the activated carbon can achieve better capacity performance while maintaining better initial coulomb efficiency and smaller expansion, which can greatly meet the commercial application level. BRIEF DESCRIPTION OF THE DRAWINGS
[0076] Figure 1 This is a scanning electron microscope image of the silicon-carbon composite material obtained in Example 6.
[0077] Figure 2 This is the first charge and discharge curve of the silicon-carbon composite material obtained in Example 6. DETAILED DESCRIPTION
[0078] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.
[0079] Example 1
[0080] (1) Phenolic resin (phenolic resin model 2123, purchased from Shandong Jiaqi Chemical Co., Ltd.) was pre-oxidized at 130°C for 2 hours in an air atmosphere, carbonized at 550°C for 1 hour in a nitrogen atmosphere (gas flow rate of 20 mL / min), and the rate of heating from the pre-oxidation temperature to the carbonization temperature was 4°C / min. After cooling to room temperature, the particles below the 60-mesh sieve and above the 80-mesh sieve were screened out, and then steam activated at 650°C (the rate of heating from room temperature to the activation temperature was 3°C / min) for 1 hour in a nitrogen atmosphere (gas flow rate of 20 mL / min) to obtain activated carbon. The specific surface area of the activated carbon obtained is 1100-1150 m 2 / g, micropore volume is 300-360mm 3 / g.
[0081] (2) Wash the activated carbon with distilled water to remove inorganic impurities on its surface, then wash it with a 2% by mass nitric acid aqueous solution to remove organic impurities on its surface, then wash it with distilled water until it is neutral, and dry it in an oven at 120 °C. Add 5 g of 1,3-diaminoguanidine hydrochloride, 10 g of potassium carbonate and 300 mL of n-butanol into a three-necked flask, heat it to 60 °C, and stir it for 1 hour. After cooling to room temperature, add 100 g of activated carbon and stir evenly, transfer it to a microwave reactor, fix the microwave frequency to 700 W, and react at 80 °C for 20 min. Cool it naturally to room temperature, wash it with deionized water by centrifugation, collect the precipitate and dry it in a constant temperature drying oven at 60 °C for 24 h to obtain modified activated carbon.
[0082] (3) 1 kg of modified activated carbon was placed in a fluidized bed, and the temperature was raised from room temperature to 500°C at a heating rate of 3°C / min, and silane was then introduced at a silane flow rate of 20 L / min for 330 min to deposit silicon in the modified activated carbon. After naturally cooling to room temperature, a silicon-carbon composite material was obtained. The mass volume ratio of the modified activated carbon to the silane was 1 kg:6600 L.
[0083] The yield of the silicon-carbon composite material is 29% and the specific surface area is 5.1m 2 / g, D50 is 8.5μm; at the current density of 0.1C, the assembled battery has a capacity of 1900.8mAh / g and a coulombic efficiency of 89.8%.
[0084] Example 2
[0085] The only difference from Example 1 is that the mass of 1,3-diaminoguanidine hydrochloride in step (2) is 10 g.
[0086] Example 3
[0087] The only difference from Example 1 is that the mass of 1,3-diaminoguanidine hydrochloride in step (2) is 15 g.
[0088] Example 4
[0089] The only difference from Example 1 is that the mass of 1,3-diaminoguanidine hydrochloride in step (2) is 20 g.
[0090] Example 5
[0091] The only difference from Example 2 is that step (3) further includes the following steps:
[0092] (4) Preparation of Ti using in-situ etching method 3 AlC 2 Mxene material. Mix 20g NaF with 500mL 9M hydrochloric acid solution and stir for 20min. Add 10g Ti 3 AlC 2 The powder (400 mesh) was stirred in a water bath at 60°C for 48 h to etch off the aluminum layer, and then washed repeatedly by centrifugation at 3500 rpm with deionized water. An appropriate amount of deionized water was added to re-disperse the bottom precipitate, and the MXene was separated by hand shaking for 5 min, and then vacuum filtered to obtain a single layer of Ti 3 C 2 Mxene nanosheets are dried in a freeze-drying oven to obtain Mxene materials.
[0093] (5) 10 g of the silicon-carbon composite material obtained in step (3) and 2 g of the Mxene material obtained in step (4) were placed in a ball mill and subjected to mechanical grinding for 48 hours. The ball mill was operated at a speed of 600 rpm / min, the ball-to-material ratio was 25:1, and the ball and ball jar were made of natural agate, with a diameter of 6-8 nm. Finally, the obtained powder was placed in a CVD, and coated at 500°C for 2 h under a nitrogen atmosphere at a heating rate of 5°C / min to obtain a silicon-carbon composite material.
[0094] The yield of the silicon-carbon composite material is 29% and the specific surface area is 4.0m 2 / g, D50 is 8.4μm; the assembled battery has a capacity of 2116.6mAh / g and a coulombic efficiency of 91.2% at a current density of 0.1C.
[0095] Example 6
[0096] The only difference from Example 5 is that the mass of 1,3-diaminoguanidine hydrochloride in step (2) is 10 g; and the mass of Mxene material in step (5) is 4 g.
[0097] Example 7
[0098] The only difference from Example 5 is that the mass of 1,3-diaminoguanidine hydrochloride in step (2) is 10 g; and the mass of Mxene material in step (5) is 6 g.
[0099] Example 8
[0100] The only difference from Example 7 is that the mass of the Mxene material in step (5) is 8 g.
[0101] Example 9
[0102] The only difference from Example 7 is that the mass of the Mxene material in step (5) is 4 g and the coating temperature is 400°C.
[0103] Example 10
[0104] The only difference from Example 6 is that the mass of the Mxene material in step (5) is 4 g and the coating temperature is 600°C.
[0105] Embodiment 11
[0106] The only difference from Example 6 is that step (4) and step (5) are replaced by the following steps: the silicon-carbon composite material (10 g) obtained in step (3) is placed in a rotary kiln, acetylene and nitrogen are introduced (the gas flow rates of acetylene and nitrogen are 20 L / min and 10 L / min, respectively), the temperature is increased to 530°C at a heating rate of 3°C / min, and the coating is carried out for 12 hours to deposit a carbon layer on the surface to obtain a silicon-carbon composite material.
[0107] The yield of the silicon-carbon composite material is 27% and the specific surface area is 4.6 m 2 / g, D50 is 8.3μm; the assembled battery has a capacity of 2015mAh / g and a coulombic efficiency of 90.3% at a current density of 0.1C.
[0108] Example 12
[0109] The only difference from Example 6 is that the time for introducing silane in step (3) is 300 min.
[0110] Embodiment 13
[0111] The only difference from Example 6 is that the microwave reaction time in step (2) is 10 min.
[0112] Embodiment 14
[0113] The only difference from Example 6 is that the temperature of the microwave reaction in step (2) is 40 min.
[0114] Embodiment 15
[0115] (1) Phenolic resin (phenolic resin model 2123, purchased from Shandong Jiaqi Chemical Co., Ltd.) was pre-oxidized at 130°C for 2 hours in an air atmosphere, carbonized at 550°C for 1 hour in a nitrogen atmosphere (gas flow rate of 20 mL / min), and the rate of heating from the pre-oxidation temperature to the carbonization temperature was 4°C / min. After cooling to room temperature, the particles below the 60-mesh sieve and above the 80-mesh sieve were screened out, and then steam activated at 650°C (the rate of heating from room temperature to the activation temperature was 3°C / min) for 1 hour in a nitrogen atmosphere (gas flow rate of 20 mL / min) to obtain activated carbon. The specific surface area of the activated carbon obtained is 1100-1150 m 2 / g, micropore volume is 300-360mm 3 / g.
[0116] (2) Wash the activated carbon with distilled water to remove inorganic impurities on its surface, then wash it with a 2% by mass nitric acid aqueous solution to remove organic impurities on its surface, then wash it with distilled water until it is neutral, and dry it in an oven at 120°C. Add 100g of activated carbon and 300mL of n-butanol into a three-necked flask, heat it to 60°C, and stir it with electromagnetic stirring for 1 hour. After cooling to room temperature, add 100g of activated carbon and stir evenly, transfer it to a microwave reactor, fix the microwave frequency to 700W, and react at 80°C for 20min. Cool it naturally to room temperature, wash it with deionized water by centrifugation, collect the precipitate and dry it in a constant temperature drying oven at 60°C for 24h to obtain modified activated carbon.
[0117] Comparative Example 1
[0118] The only difference from Example 1 is that step (2) is omitted. The yield of the silicon-carbon composite material is 29% and the specific surface area is 4.4 m 2 / g, D50 is 8.5μm; the assembled battery has a capacity of 1818.2mAh / g and a coulombic efficiency of 88.6% at a current density of 0.1C.
[0119] Effect Example 1
[0120] The modified activated carbons prepared in the examples and comparative examples were tested for specific surface area, micropore volume, micropore, mesopore and macropore ratio, guanidine content, amino content and nitrogen content.
[0121] The specific surface area was tested by weighing 0.1 g of the modified activated carbon obtained in the above embodiments and comparative examples with weighing paper, and conducting nitrogen adsorption and desorption tests in a Micromeritics ASAP2460 adsorption and desorption instrument, wherein the degassing temperature was 300°C, the degassing time was 4 hours, and the adsorption atmosphere was nitrogen.
[0122] The testing method for micropore volume is: using a specific surface area and pore size micropore analyzer for testing, using the nitrogen adsorption method, nitrogen molecules are physically adsorbed on the surface of the modified activated carbon under low temperature conditions, and the nitrogen adsorption amount under different pressures is measured. The nitrogen adsorption isotherm is drawn, and combined with the theoretical model (BET model, BJH model), the volume of the pores of the modified activated carbon during the micropore filling process can be obtained.
[0123] The test method for the proportion of micropores, mesopores and macropores is: using the nitrogen adsorption method, using the adsorption layer formed by nitrogen on the solid surface to determine the pore size and pore volume. The modified activated carbon is placed in a nitrogen adsorption instrument, and nitrogen is introduced at 300°C to make it adsorb on the sample surface. The adsorption amount and adsorption isotherm can be obtained by analyzing the change in nitrogen pressure before and after adsorption, and the pore size distribution can be obtained.
[0124] The test method for the guanidine content is: using mass spectrometry to measure the mass-to-charge ratio of the modified activated carbon. The modified activated carbon obtained in the embodiment and the comparative example is rinsed with deionized water for 10 minutes, and after removing the surface sediment and soluble impurities, it is ground and dried to obtain a modified activated carbon form suitable for mass spectrometry analysis, and then injected into a mass spectrometer for analysis. After the modified activated carbon is ionized into ions, it is deflected or separated in an electric field or magnetic field. The mass-to-charge ratio and abundance information of the modified activated carbon are determined according to the mass spectrum, and the guanidine content is calculated by comparing the standard spectrum or database.
[0125] The amino content was determined by dissolving the modified activated carbon prepared in the examples and comparative examples in deionized water and titrating the mixture using a potentiometric titrator. The potential change during the titration was measured and recorded using the potentiometric titrator, and the amino content was calculated based on the titration curve.
[0126] The testing method for nitrogen content is: using an element analyzer to determine the nitrogen content in the modified activated carbon.
[0127] The test results are shown in Table 1.
[0128] Table 1
[0129]
[0130] Effect Example 2
[0131] Figure 1 This is a SEM image of the silicon-carbon composite material obtained in Example 6. Figure 1It can be seen that the modified activated carbon is obtained after the phenolic resin is modified by 1,3-diaminoguanidine hydrochloride, and the modified activated carbon forms block particles after silane adsorption, and then coated with Mxene material to form a lamellar structure on the surface. The silicon-carbon composite material finally obtained is a block particle with a lamellar structure on the surface.
[0132] The yield of the silicon-carbon composite material obtained in the above examples and comparative examples was tested. The yield was the percentage obtained by dividing the mass of the silicon-carbon composite material obtained by the mass of the phenolic resin in step (1).
[0133] The specific surface area of the silicon-carbon composite material obtained in the above embodiment and comparative example was tested using Micromeritics ASAP2460 adsorption-desorption instrument. The test method is: weigh 0.1g of the silicon-carbon composite material obtained in the above embodiment and comparative example with weighing paper and conduct nitrogen adsorption-desorption test, wherein the degassing temperature is 300°C, the degassing time is 4h, and the adsorption atmosphere is nitrogen.
[0134] The D50 particle size of the silicon-carbon composite materials obtained in the above examples and comparative examples was tested using a Malvern 3000 laser particle size analyzer.
[0135] The test method for obtaining the interlayer spacing by XRD test is: first, the silicon-carbon composite material obtained in the above embodiment and comparative example is flattened on the surface of a glass slide, and flattened with another glass slide, and then the powder XRD test is performed using Bruker's D8DISCOVER instrument, with a test range of 10-70° and a scanning speed of 5° / min. The angle corresponding to the 002 peak in the XRD spectrum is 2θ, and then the Bragg equation 2dsinθ=λ is used to calculate the interlayer spacing d of the sample; wherein λ represents the wavelength of the incident X-ray, and θ is the angle between the incident ray, the reflected ray and the reflected crystal plane.
[0136] The testing method of micropore volume is as follows: the specific surface area and pore size micropore analyzer is used for testing. The nitrogen adsorption method is adopted. Nitrogen molecules are physically adsorbed on the surface of the silicon-carbon composite material under low temperature conditions. The nitrogen adsorption amount under different pressures is measured and the nitrogen adsorption isotherm is drawn. Combined with the theoretical model (BET model, BJH model), the pore volume of the silicon-carbon composite material during the micropore filling process can be obtained.
[0137] The above test results are shown in Table 2.
[0138] Table 2
[0139]
[0140] The silicon-carbon composite materials prepared in the above examples and comparative examples were tested for nitrogen content, oxygen content, silicon content, carbon content and particle size of silicon nanoparticles.
[0141] The test results are shown in Table 3.
[0142] Table 3
[0143]
[0144] Effect Example 3
[0145] The silicon-carbon composite materials prepared in the above examples and comparative examples were respectively used as negative electrode materials and lithium metal sheets to assemble into half-cell tests, and the electrolyte was 1M NaFP 6 The solution (solvent is diethylene glycol dimethyl ether (Diglyme) and the separator is glass fiber (GF / A). At a temperature of 25°C and a current density of 0.1C, the assembled half-cell was tested for charge and discharge cycles using a blue electric test instrument to obtain data on its reversible specific capacity and first coulombic efficiency.
[0146] The expansion test method is: add 7.5g conductive graphite (SFG-6), 2.5g conductive carbon black (SP), 33.3g aqueous binder (LA132) to 120g water, set the dispersing machine stirring speed to 2000rpm / min, stir for 0.5h, then add 35g silicon-carbon composite material, continue stirring for 2.5h, and obtain slurry. The prepared slurry is evenly coated on the metal foil (aluminum foil is used for the positive electrode and copper foil is used for the negative electrode) to form a thin film. After coating, it needs to be allowed to stand until there is no obvious solvent on the surface before being placed in a vacuum drying oven for drying. In order to ensure that the electrode coating reaches a certain thickness, a special coating thickness adjustment roller and reverse rolling are used to ensure the uniformity and thickness of the coating. The dried electrode sheet is cut into the specified size with a roller cutter to obtain the electrode sheet, and the test electrode sheet thickness is H1. With 1M LiPF 6 (The solvent was EC (ethylene carbonate): EMC (ethyl methyl carbonate) volume ratio = 3:7 and 10% FEC (fluoroethylene carbonate) as the electrolyte, Celgard 2400 membrane as the separator, and lithium sheet as the counter electrode. In a vacuum glove box [w(H 2 O)<0.1×10 -4 %, w(O 2 )<0.1×10 -4 %], CR2025 button half-cell was assembled and subjected to discharge-charge-re-discharge, discharge: 0.1C to 0.01V, rest for 10min, charge: 0.1C to 1.5V; the battery was disassembled and the electrode thickness H2 was tested, the expansion rate = (H2-H1) / H1×100%.
[0147] The results are shown in Table 4 and Figure 2 shown.
[0148] Table 4
[0149]
[0150] Based on the above embodiments and comparative examples, it can be seen that embodiments 1 to 4 are 1,3-diaminoguanidine hydrochloride modified silicon-carbon composite materials, and embodiments 5 to 10 are 1,3-diaminoguanidine hydrochloride modified silicon-carbon composite materials coated with Mxene. Comparative Example 1 is a silicon-carbon composite material that has not been modified with 1,3-diaminoguanidine hydrochloride, and Embodiment 11 is a 1,3-diaminoguanidine hydrochloride modified silicon-carbon composite material coated with a carbon layer by CVD method.
[0151] It can be seen from Table 2 and Table 4 that, first, the specific surface area of the activated carbon modified by 1,3-diaminoguanidine hydrochloride will increase, and the micropore volume will also increase, and the mass of the added 1,3-diaminoguanidine hydrochloride should not be too low or too high. When the mass of 1,3-diaminoguanidine hydrochloride is 10g, the increase in its specific surface area and micropore volume is large, and the electrochemical performance is the best. If the mass of 1,3-diaminoguanidine hydrochloride is too low, the degree of modification of the functional groups on the surface of the activated carbon is low, and the influence of the micropore ratio is very small. The mass of 1,3-diaminoguanidine hydrochloride is too high, and the more intense the modification process is, the greater the porosity is. Secondly, the present invention uses a microwave method to modify activated carbon, and the activated carbon can produce a large number of micropores under the action of microwaves, which is conducive to the manufacture of activated carbon with rich micropores. In addition, the microwave reaction time is rapid and uniform, which can enable 1,3-diaminoguanidine hydrochloride to be quickly and uniformly modified on the surface of activated carbon. The fluidized bed process is adopted to provide good gas-solid mass transfer conditions, so that silane can be quickly and evenly deposited on the porous carbon, thereby effectively improving the capacity of the silicon-carbon negative electrode. Finally, in order to further buffer the volume expansion of the silicon-carbon negative electrode and improve the conductivity, the technical solution adopts a ball milling assembly process to wrap the Mxene material on the surface of the silicon-carbon negative electrode. On the one hand, it effectively buffers the volume expansion and yield of the silicon-carbon negative electrode material during the cyclic charge and discharge process. On the other hand, it also greatly improves the electronic conductivity of the material, so that electrons and lithium ions can be transmitted more quickly, and the capacity of the electrode material is improved. It can be seen that the activated carbon modification method provided by the present invention can well improve the surface functional groups, pore structure and later adsorption of silane of activated carbon, and then combined with the Mxene material coating process to improve the conductivity of the material, buffer the volume expansion of the electrode material, and can well improve the electrochemical lithium storage performance of the silicon-carbon material.
[0152] Figure 2 This is the first charge and discharge curve of the battery assembled with the silicon-carbon composite material prepared in Example 6 under 0.1C conditions. Figure 2It can be seen that the battery assembled with the silicon-carbon composite material begins to have a voltage slope at around 0.7V when it is discharged for the first time, which corresponds to the process of the first lithium insertion on the electrode surface to form a solid electrolyte interface film (SEI); a longer voltage platform appears at around 0.1V, corresponding to the process of lithium and silicon reacting to form a lithium silicon alloy (LixSi); during charging, the charging voltage platform of around 0.4V corresponds to the lithium removal process of the LixSi alloy. The first discharge and charging capacities of the battery assembled with the silicon-carbon composite material are 2239.6mAh / g and 2431.7mAh / g, respectively, and the coulomb efficiency is 92.1%. The irreversible capacity loss of the first cycle is mainly due to the formation of the SEI film on the surface of the electrode material, which consumes the lithium content in the electrolyte. The longer platform area also further shows that the silicon-carbon composite material has a stronger ability to insert and remove lithium.
Claims
1. A method for preparing modified activated carbon, characterized in that: It includes the following steps: The activated carbon and the solvent are subjected to microwave reaction to obtain modified activated carbon; the microwave power during the microwave reaction is 600-800W; and the microwave reaction time is 10-40min.
2. The method for preparing modified activated carbon according to claim 1, characterized in that: The preparation method of the modified activated carbon meets one or more of the following conditions: (1) The specific surface area of the activated carbon is 1100-1150m 2 / g; (2) The micropore volume of the activated carbon is 300-360mm 3 / g; (3) The activated carbon is prepared by the following method: pre-oxidizing, carbonizing and activating a phenolic resin, wherein the temperatures of the pre-oxidation, carbonizing and activating are increased in sequence; The pre-oxidation temperature is preferably 120-140°C, such as 130°C; the pre-oxidation time is preferably 1-3h, such as 2h; and the pre-oxidation is preferably carried out in air or oxygen atmosphere; Wherein, the carbonization is preferably carried out under an inert atmosphere; the inert atmosphere is preferably nitrogen; the gas flow rate of the inert atmosphere is preferably 10-30 mL / min, for example, 20 mL / min; the carbonization temperature is preferably 500-600°C, for example, 550°C; the carbonization time is preferably 0.5-1.5h, for example, 1h; the rate of heating from the pre-oxidation temperature to the carbonization temperature is preferably 3-5°C / min, for example, 4°C / min; Wherein, the activation is preferably carried out under an inert atmosphere; the inert atmosphere is preferably nitrogen; the gas flow rate of the inert atmosphere is preferably 10-30 mL / min, for example, 20 mL / min; the activation temperature is preferably 600-700°C, for example, 650°C; the activation time is preferably 0.5-1.5h, for example, 1h; the activation atmosphere is preferably water vapor; the rate of heating from room temperature to the activation temperature is preferably 2-4°C / min, for example, 3°C / min; (4) The type of the solvent is water or an alcohol solvent; the alcohol solvent is preferably one or more of isopropanol, ethylene glycol, propylene glycol and n-butanol, such as n-butanol; (5) The mass volume ratio of the activated carbon to the solvent is 1 g: (1-5) mL, preferably 1 g: (2-4) mL, for example 1 g: 3 mL; (6) The microwave power during the microwave reaction is 650-750 W, for example 700 W; (7) the temperature of the microwave reaction is 60-90°C, for example 80°C; and, (8) The microwave reaction time is 20-30 min, for example 25 min.
3. The method for preparing modified activated carbon according to claim 1, characterized in that: Preferably, a guanidine salt is also added during the microwave reaction; Wherein, the guanidine salt is preferably guanidine hydrochloride, guanidine nitrate, guanidine sulfate or guanidine carbonate; the guanidine hydrochloride is preferably aminoguanidine hydrochloride, 1,3-diaminoguanidine hydrochloride or 1-methylguanidine hydrochloride; the guanidine sulfate is preferably 1,3-diphenylguanidine sulfate or 1-(4-aminobutyl)guanidine sulfate; the guanidine carbonate is preferably 4-chlorophenylguanidine carbonate or phenylguanidine carbonate; Wherein, the mass ratio of the activated carbon to the guanidine salt is preferably (3-22):1, more preferably (4-21):1, such as 10:1, 20:1, 6.67:1 or 5:1; And / or, potassium carbonate is further added during the microwave reaction; Wherein, the mass ratio of the activated carbon to the potassium carbonate is preferably (5-15):1, for example 10:
1.
4. A modified activated carbon, characterized in that It is prepared by the modified activated carbon preparation method as described in any one of claims 1 to 3; The specific surface area of the modified activated carbon is preferably 1750-2000m 2 / g, such as 1784.3, 1878.3, 1834.2, 1798.3, 1794.1, 1884.5, or 1939.4m 2 / g; The micropore volume of the modified activated carbon is preferably 0.5-0.9 cm 3 / g, for example 0.579, 0.606, 0.583, 0.588, 0.563, 0.598 or 0.637 cm 3 / g; The micropore ratio of the modified activated carbon is preferably 78%-86%, such as 79.3%, 81.4%, 78.9%, 79.3%, 79.4%, 81.0% or 84.6%; The mesopore ratio of the modified activated carbon is preferably 10%-25%, such as 20.38%, 20.25%, 17.25%, 19.10%, 19.38%, 18.5% or 14.9%; The macropore proportion of the modified activated carbon is preferably 0.2%-2.3%, such as 1.32%, 1.35%, 0.35%, 2.00% or 0.50%; The guanidine content of the modified activated carbon is preferably 0-0.12, such as 0.04, 0.06, 0.09, 0.10, 0.07 or 0.08; The amino content of the modified activated carbon is preferably 0-3.00, such as 1.53, 1.75, 2.08, 2.46, 2.03 or 2.57; The nitrogen content of the modified activated carbon is preferably 0.10%-7.00%, for example 0.36%, 4.35%, 5.14%, 5.84%, 6.63%, 4.84% or 5.52%.
5. A method for preparing a silicon-carbon composite material, characterized in that: The method comprises the following steps: vapor-depositing the modified activated carbon as claimed in claim 4 and silane to obtain a silicon-carbon composite material.
6. The method for preparing the silicon-carbon composite material according to claim 5, characterized in that: The method for preparing the silicon-carbon composite material meets one or more of the following conditions: (1) The temperature of the vapor deposition is 400-600°C, for example 500°C; (2) The vapor deposition time is 300-400 min, for example 330 min; (3) The rate of heating from room temperature to the vapor deposition temperature is 2-4°C / min, for example 3°C / min; (4) the mass volume ratio of the modified activated carbon to the silane is 1 kg: (3000-12000) L, for example 1 kg: 6000 L or 1 kg: 6600 L; and, (5) After vapor deposition of the modified activated carbon as claimed in claim 4 and silane to obtain the silane composite material A, the step of coating with MXene material or carbon is also included; Wherein, when MXene material is used for coating, the mass ratio of the silane composite material A to the MXene material is preferably 1:(0.2-0.8), for example, 1:0.4 or 1:0.6; Wherein, when MXene material is used for coating, the coating method is preferably vapor deposition; the coating is preferably carried out under an inert atmosphere; the inert atmosphere is preferably nitrogen; When MXene material is used for coating, the coating temperature is preferably 400-600°C, for example, 500°C; the rate of heating from room temperature to the coating temperature is preferably 4-6°C / min, for example, 5°C / min; the coating time is preferably 1-3h, for example, 2h; Among them, when carbon coating is adopted, the coating method is preferably gas phase coating; the carbon source in the gas phase coating is preferably acetylene; the gas carbon source is preferably also introduced into a carrier gas; the type of the carrier gas is preferably nitrogen; the volume ratio of the gas carbon source and the carrier gas is preferably (1-3):1, for example, 2:1; the mass volume ratio of the silicon-carbon composite material and the carbon source is preferably 1g:(1000-2000)L, for example, 1g:1440L; the temperature of the carbon coating is preferably 500-560°C, for example, 560°C; the time of the carbon coating is preferably 10-14h, for example, 12h; the rate of heating from room temperature to the carbon coating temperature is preferably 2-4°C / min, for example, 3°C / min.
7. A silicon-carbon composite material, characterized in that: It is prepared by the method for preparing the silicon-carbon composite material as claimed in claim 5 or 6; The specific surface area of the silane composite material is preferably 4.0-5.4 m 2 / g, such as 4.1, 4.2, 4.6, 4.7, 4.8, 4.9, 5.0, 5.1 or 5.3m 2 / g; The D50 of the silane composite material is preferably 7.5-8.7 μm, such as 8.6, 8.5, 8.4, 8.3, 8.0, 7.9 or 7.8 μm; The interlayer spacing of the silane composite material is preferably 0.2-0.4, such as 0.301, 0.299, 0.298, 0.296, 0.293, 0.291, 0.287, 0.285, 0.283, 0.279, 0.269 or 0.267; The micropore volume of the silane composite material is preferably 0.4-0.8 cm 3 / g, for example, 0.749, 0.747, 0.746, 0.692, 0.672, 0.678, 0.648, 0.618, 0.616, 0.608, 0.593, 0.579, 0.511 or 0.
496.
8. A pole piece, characterized in that: It comprises the silicon-carbon composite material as claimed in claim 7.
9. Use of the electrode piece according to claim 8 in an electrochemical device.
10. An electrochemical device, characterized in that: It comprises the pole piece as claimed in claim 8.
Citation Information
Patent Citations
Preparation method of carbon-silicon negative electrode material and lithium ion battery
CN107910540A
Low-temperature-resistant lithium ion battery containing activated carbon negative electrode material and preparation method of low-temperature-resistant lithium ion battery
CN117317188A
Technology for preparing high nitrogenous functional group activated carbon through phosphoguanidine activation method
CN103112853A
Method for efficiently preparing cotton based mesoporous activated carbon fiber
CN105480973A
Preparation method of microwave radiation enhancement alkali-modified carbon-supported noble metal catalyst for production of cinnamyl alcohol by means of selective hydrogenation
CN109225209A